PENGARUH PEMANFAATAN BUAH MENGKUDU (Morinda citrifolia L) TERHADAP PENYEMBUHAN KETOMBE KERING - SUSANTI, TETI; rahmiati, rahmiati; yuliana, yuliana (Faculty of Tourism and Hospitality - Universitas Negeri Padang, 2013)
This study aimed to analyze the use of noni fruit to cure dry dandruff whichwas measured from the level of skin itching of the head, the amount of crust/dandruff, scalp conditions and hair loss levels. There are three kind of treatment onthis research that was the control group, the first experimental group and secondexperimental group. The type of research was quasi experimental study withNonequivalent Control Group Design and the technique sampling was purposivesampling voluntarily. The sample was nine of UNP students who indicated sufferingfrom dry dandruff. Data analysis was analytical Varian and Duncan test. The resultsshowed that the cure in the control group did not show a change for better progress inevery indicator. On the contrary, the first and the second experimental groups showedsignificant result in every indicator. As a result, the use of noni fruit can cure drydandruff on the first experimental group with treatment once in a day. Â